Nilai-Nilai Sosial dalam Tradisi Suna Ro Ndoso Suku Mbojo (Studi Kasus di Desa Kempo Kecamatan Kempo Kabupaten Dompu) - Arminsyah A; Muh. Zubair; Bagdawansyah Alqadri; Sawaludin S (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study aims to (1) examine the implementation process of the Suna Ro Ndoso tradition of the Bima (Mbojo) people in Kempo Village, Kempo District, Dompu Regency, and (2) identify the social values embodied in the Suna Ro Ndoso tradition of the Bima (Mbojo) people in Kempo Village, Kempo District, Dompu Regency. This study employs a qualitative research approach using a descriptive method. Data collection techniques included observation and interviews, while data analysis involved data reduction, data presentation, and drawing conclusions. The results indicate that: (1) The implementation process of the Suna Ro Ndoso tradition among the Mbojo people in Kempo Village, Kempo District, Dompu Regency, consists of two stages: Mbolo ro Kaboro Weki (family deliberation) and the Suna Ro Ndoso ceremony sequence. The Mbolo Weki stage comprises several events, namely ceremony preparations and the circumcision procession itself. Subsequently, the Suna Ro Ndoso ceremony sequence includes Ngaji Jamak (communal Quran recitation), Compo Sampari, Suna Ro Ndoso (the circumcision ritual), and Mbolo (the celebratory feast). (2) The Suna Ro Ndoso tradition of the Mbojo people in Kempo Village, Kempo District, Dompu Regency, embodies specific values. These include religious values, cultural values, values of mutual assistance, values of cooperation, and aesthetic values.